Analisis Perkembangan Usaha Pabrik Tahu Bandarejo Dusun 3 dari Perspektif Ekonomi Islam - Yuni Kartika; Fawza Rahmat; Maisarah Leli (Transformasi: Journal of Economics and Business Management, 2024)
Bandarejo Tofu Factory, Dusun 3 is an example of a micro-enterprise that has developed by utilizing local resources. From an Islamic economic perspective, the development of this business reflects the application of sharia principles, such as justice, social welfare, and sustainable resource management. Islamic economics emphasizes the balance between profit and fair distribution, and avoids detrimental practices, such as usury and monopoly. This factory plays a role in creating jobs and supporting the local economy by using soybean raw materials from local farmers. The production process that is in accordance with Islamic law makes this business meet the halal criteria, while its orientation towards social desires and responsibilities reflects the values ​​of Islamic economics. However, the main challenge faced is maintaining Islamic ethical principles, such as honesty in transactions and concern for worker welfare, amidst competitive economic competition. This study aims to analyze the dynamics of the development of the Bandarejo Tofu Factory, Dusun 3 from an Islamic economic perspective, in order to contribute to the development of micro-enterprises based on sharia values. This study uses a qualitative approach with primary data obtained through interviews and documentation. The main informant is the factory owner, Mrs. Atin. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that the development of the Bandarejo Dusun 3 Tofu Factory has made a significant contribution to the community's economy through marketing and capital strategies. In addition to increasing economic income, this business also absorbs local workers and helps reduce poverty levels in the Bandarejo Dusun 3 area.